2014
DOI: 10.1002/mc.22162
|View full text |Cite
|
Sign up to set email alerts
|

Increased androgen receptor gene copy number is associated with TMPRSS2-ERG rearrangement in prostatic small cell carcinoma

Abstract: Small cell carcinoma of the prostate (PSCC) is a highly aggressive malignancy that often develops in patients previously treated with hormonal therapy for metastatic prostatic acinar adenocarcinoma. The TMPRSS2-ERG gene rearrangement is highly specific for prostate cancer and shared by PSCC; however, the role of androgen receptor (AR) gene alterations and interaction with TMPRSS2-ERG rearrangement are incompletely understood in PSCC. Sixty-one cases of PSCC were examined for AR gene copy number and TMPRSS2-ERG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 59 publications
3
11
0
Order By: Relevance
“…Detection of higher AR transcription in T2E fusion positive patients is likely to be explained by this association. Similarly, the increased AR gene copy number was associated with T2E rearrangement in prostatic small cell carcinoma . These results were also confirmed by prostate cancer cell culture studies .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Detection of higher AR transcription in T2E fusion positive patients is likely to be explained by this association. Similarly, the increased AR gene copy number was associated with T2E rearrangement in prostatic small cell carcinoma . These results were also confirmed by prostate cancer cell culture studies .…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, the increased AR gene copy number was associated with T2E rearrangement in prostatic small cell carcinoma. 55 These results were also confirmed by prostate cancer cell culture 59 Although these findings were important in terms of confirming the compatibility of the study, we revealed that KLK3 did not predict PC risk at the RNA level in ASAP-diagnosed patients.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, the possible H-score ranged from 0 to 300 (20). Currently there is no consensus cutoff for p53 immunohistochemistry in CRC.…”
Section: Tissue Microarray and Immunohistochemistrymentioning
confidence: 99%
“…ERG (ETS-related gene) and TMPRSS2 are 2 of the 29 members of the ETS family of genes, which plays a crucial role in the development of different tissues as well as cancer progression. Approximately half of the usual PCa and SmCC present TMPRSS2-ERG gene fusion [36] or other ERG gene rearrangements [36][37][38]. Tan and colleagues evaluated the status of RB1, TP53, and PTEN in SmCC.…”
Section: Novel Morphologic Classificationmentioning
confidence: 99%